2022
DOI: 10.1155/2022/7928344
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of Combined Detection of Pelvic Ultrasound and Serum LH, FSH, and E2 Levels in Children with Idiopathic Central Precocious Puberty

Abstract: Objective. To study the diagnostic value of combined detection of pelvic ultrasound and serum LH, FSH, and E2 levels in children with idiopathic central precocious puberty (ICPP). Methods. 30 cases of children with ICPP admitted to our hospital from January 2019 to January 2021 were selected as the experimental group, and 30 healthy people during the same period were selected as the control group. Both groups received pelvic ultrasound and serum LH, FSH, and E2 detection; the two groups were compared in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the evaluation of LH peaks after GnRH testing is the gold standard in the biochemical diagnosis of CPP. The combined detection of secondary sexual characters, bone age, hormone levels, pelvic ultrasound and cranial MRI could increase the sensitivity and accuracy for CPP diagnosis (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the evaluation of LH peaks after GnRH testing is the gold standard in the biochemical diagnosis of CPP. The combined detection of secondary sexual characters, bone age, hormone levels, pelvic ultrasound and cranial MRI could increase the sensitivity and accuracy for CPP diagnosis (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology analysis revealed that the core active ingredients in ZBDHP, including tetrahydropalmatine, alisol C, 25‐anhydroalisol A 11‐acetate, hispidone, cavidine, alisol E, melianone, neogitogenin, denudatin B, and 16β‐hydroperoxyalisol B, can help mitigate the formation of precocious puberty. A relevant study has shown that the levels of serum luteinizing hormone (LH), follicle stimulating hormone (FSH), and estradiol (E 2 ) in the CPP group were significantly higher than those in the normal control group 42 . FSH stimulates follicle growth, and LH promotes both oocyte maturation and ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…In menstural cycle there are two phase proliferative phase and secreatory phase, day 1-6 bleeding phase after the that FSH nourhies the ovaries to produce egg, it has millions of egg of that healthy fully matured egg is release by the graffian follicle [36]. The LH is more important in the rupture of graffian follicle to release the mature egg into the fallopian tubes at the day 14 [37]. The graffian follicle has progesterone producing hormone which releases the progesterone which makes the endometrium (the tremendous supply of blood along the side of endometrium to implant the fertilized egg ) if the egg gets fertilized it will get implanted into the endometrium and the corpus luteum continues to secrete progesterone until the labour [38].…”
Section: Hormonal Factors Responsible For Breast Cancermentioning
confidence: 99%